Preferences and perceptions of students about the degree in Social Work - Morcillo Martínez, Juana María; Ochando Ramírez, María Victoria; Martínez Salvador, Isabel María (Social Work Education, 2023)
The Social Work Degree prepares students for their future professional practice. Considering the students’ point of view helps to gather their impressions. It also makes it possible to improve and make teaching and institutional decisions. The aim of this study is to explore the perceived quality of the students of the Degree in Social Work taught in the Public Universities of the Autonomous Community of Andalusia (Spain). For this purpose, we have chosen to carry out an exploratory study with a qualitative approach. A non-probabilistic sample of 73 participants made up of students from various courses was used. The instrument used was a questionnaire of open questions elaborated in Microsoft Forms and distributed telematically. The results show a high level of satisfaction with the Social Work studies received. The opinions have made it possible to extract categories of analysis on overall satisfaction, methodology, content, teaching staff, and the link between training and professional practice. The study show which dimensions they consider to contribute quality to their studies, showing a preference for practical issues. They emphasize their interest in participatory teaching methodologies, updated content and teaching staff who are involved in their teaching practice that will enable their future professional practice.
Keywords: perception; quality of education; Social Work; student body; university; Scopus; Emerging